Հետագայի գրությունները արաբերեն ձեռագրերում․ Ձեռագրագիտական հարցեր - Մակարյան, Վեներա
In addition to the textual and manuscript value, the history of the manuscript is also significant and interesting. Evidence of this can be found in colophons and manuscript notes. This article deals with manuscript notes as a source of socio- economic, political, historical, topographical, and biographical information. Such notes mention personal names, dates of birth and death, kinship ties, geographical names, and prices of goods in the given settlement during a certain period. Additionally, they include various terms related to the fields of craft and trade. Manuscript notes are located throughout the text, primarily at the beginning and end of the text block. In some cases, the entire page is covered with such information. These notes serve as termini ante quem in the absence of a colophon, allowing for the possible determination of the manuscript’s writing time. This study highlights the precise classification of manuscript notes in Arabic codicology. Their collation with similar scripts in Armenian reveals commonalities and peculiarities of these traditions. История рукописи засвидетельствована в колофонах и других записях. Это богатый источник социально-экономических, политических, исторических, топографических и биографических сведений: в них упоминаются личные имена, даты рождения, смерти и других событий, родственные связи, географические названия, цены товаров в данном населенном пункте в определенный период, термины, относящиеся к ремеслам и торговле. Записи встречаются на различных страницах и в разных разделах рукописи, но чаще всего пишутся в начале и конце блока, в фронтальной части; в некоторых случаях такой информацией бывает покрыта вся страница. При отсутствии колофона, записи в рукописях служат termini ante quem: благодаря им становится возможным примерно определить время написания рукописи. В арабской кодикологии рубрика записи в рукописи с формальной точки зрения имеет четкую характеристику. Их сравнение с аналогичными записями на армянском языке обнаруживает как общие черты, так и различие традиций.
Keywords: Ձեռագրագիտություն